2021
DOI: 10.2147/opth.s341516
|View full text |Cite
|
Sign up to set email alerts
|

Digital Survey Assessment of Factors Associated with Musculoskeletal Complaints Among US Ophthalmologists

Abstract: Purpose To quantify features of musculoskeletal (MSK) complaints among US ophthalmologists and analyze factors related to symptom severity. Methods Cornea, glaucoma, retina, and comprehensive practitioners were invited to complete a web-based survey via email. Data on demographics, practice and procedural volumes, wellness activities, job stress, MSK health, the Total Disability Index (TDI), and ergonomics were collected. Significance testing was performed to evaluate f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 18 publications
(39 reference statements)
0
17
0
Order By: Relevance
“…Furthermore, 9.6% suffered from reduced working hours and 1.2% eliminated surgery from their practice altogether. 10 Weinstock et al 12 studied the musculoskeletal complaints of 25 anterior segment surgeons: 77% reported that 3D HUD reduces the severity and frequency of their musculoskeletal pain. The surgeons included in this study, however, had varying weekly surgical volume and 3D HUD cataract experience.…”
Section: Advantages Of 3d Hud-based Cataract Surgery Improved Ergonomicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, 9.6% suffered from reduced working hours and 1.2% eliminated surgery from their practice altogether. 10 Weinstock et al 12 studied the musculoskeletal complaints of 25 anterior segment surgeons: 77% reported that 3D HUD reduces the severity and frequency of their musculoskeletal pain. The surgeons included in this study, however, had varying weekly surgical volume and 3D HUD cataract experience.…”
Section: Advantages Of 3d Hud-based Cataract Surgery Improved Ergonomicsmentioning
confidence: 99%
“…Tan et al10 reported that of 245 ophthalmologists, 81.4% reported musculoskeletal pain, discomfort, or disability, which was commonly exacerbated by surgery. Furthermore, 9.6% suffered from reduced working hours and 1.2% eliminated surgery from their practice altogether 10. Weinstock et al12 studied the musculoskeletal complaints of 25 anterior segment surgeons: 77% reported that 3D HUD reduces the severity and frequency of their musculoskeletal pain.…”
Section: Advantages Of 3d Hud-based Cataract Surgerymentioning
confidence: 99%
“…The survey from which the current paper's findings are derived is the same survey described in a previous publication. 8 Implied consent was obtained by informing participants of the purpose, data usage, anonymity, and voluntariness of the study preceding survey administration. No incentives were provided, and participants could exit the survey at any time.…”
Section: Ethodsmentioning
confidence: 99%
“…From a survey of mostly high-volume ophthalmologists in the United States, it was found that 81.4% of participants experienced episodes of pain, discomfort, or disability. 8 Respondents endorsed moderate-to-severe work-related stress on average, which was significantly linked to the extent of their symptoms. In response to MSK complaints, the most selected actions were physical maneuvers such as stretching, exercise, and operating room (OR) postural adjustments.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation